A VISION FOR CYBERINFRASTRUCTURE. (Computer (00189162), 2009)
This article discusses the work of the U.S. National Science Foundation Office of Cyberinfrastructure, which is working to create high-performance computing (HPC) systems for scientific research. The development of supercomputing centers around the country on the Open Science Grid is described. The challenges associated with developing software systems that can be used to interpret the volume of information collected by data-intensive systems is described.